Assistance in Commemorating Ashura in Kampung Nangka Bugang: Efforts to Preserve Tradition, Meaning, and Social Cohesion - Nuryanto, Uli Wildan; Subroto, Desty Endrawati; Ningsih, Rastia; Fiana, Marista; Komariah, Ade; Fikri, Riri Ukhtul; Muti'ah, Eva; Azzi, Muhamad Fahmi; Masitoh, Siti; Hanifah,; Basrowi, (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This research aims to explore the implementation and significance of Ashura commemoration in Nangka Bugang Village, highlighting its role in preserving Islamic traditions and fostering social cohesion within the local community. Method: The study utilized participatory observation and in-depth interviews with community leaders to understand the rituals and social values associated with Ashura in this region. Practical Application: The findings emphasize Ashura’s role in strengthening community bonds. This research can inform efforts to preserve cultural traditions and enhance social unity in similar communities. Conclusion: Ashura commemoration in Nangka Bugang Village is both a spiritual and social event, contributing to cultural preservation and community solidarity. The study provides insights into the importance of religious observances in promoting social cohesion.